182k views
3 votes
Help!


image

User Marsha
by
5.3k points

1 Answer

2 votes


t^2(\mathrm dy)/(\mathrm dt)+y^2=ty

Divide both sides by
y^2:


(t^2)/(y^2)(\mathrm dy)/(\mathrm dt)+1=\frac ty

Let
z(t)=\frac t{y(t)}, so that
y=\frac tz and


(\mathrm dy)/(\mathrm dt)=(z-t(\mathrm dz)/(\mathrm dt))/(z^2)

so that the ODE is transformed to


z^2(z-t(\mathrm dz)/(\mathrm dt))/(z^2)+1=z


z-t(\mathrm dz)/(\mathrm dt)+1=z

and assuming
t>0,


(\mathrm dz)/(\mathrm dt)=\frac1t

The remaining ODE is separable:


\mathrm dz=\frac{\mathrm dt}t\implies z=\ln t+C


\implies\frac ty=\ln t+C


\implies\frac yt=\frac1{\ln t+C}


\implies y=\frac t{\ln t+C}

User Janaaaa
by
5.2k points